Answer:
m = 
Step-by-step explanation:
Given
y = mx + b ( subtract b from both sides )
y - b = mx ( divide both sides by x )
= m
The basic form of the equation is:
4p(x-h) = (y-k)2
(h,k) is the vertex
4(-0.5)(x-1.5) = (y-(-4))2
-2(x-1.5) = (y+4)2
-2(x-1.5) = y2 + 8y + 16
x - 1.5 = (-1/2)(y2 + 8y + 16)
x = (-1/2)y2 - 4y - 8 + 1.5
x = (-1/2)y2 - 4y - 6.5
get a journal and pencil and when you go to sleep, don't put on any alarms. then write down in the morning what you dreamt about. every detail you can thing of. if you have the dream again, write down more details. this will help you begin to lucid dream.
Answer:158.99
Step-by-step explanation:
Answer:
Step-by-step explanation:
find f(x) first because it is in the parenthesis